Oblivion or utopia the prospects for Africa - Malunga, Chiku Watchman (Lanham, MD University Press of America, 2010)
This book explains that efforts to reverse Africa's continuing underdevelopment have failed to date because they have not been consciously aimed at enabling Africa to turn its vast natural resources into wealth; here, Malunga proposes a five step strategy enabling the continent revolutionize and improve the system.
Includes index
Keywords: Africa -Economic conditions -21st century